MULTI STAGE SHRINKING CORE MODEL FOR PHASE CONVERSION TOWARDS YTTRIUM IRON GARNET - Anthoni Stanpo, Vito
Yttrium Iron Garnet (YIG) is a soft ferrite commonly used for the high-frequency circulator.YIG usually is made through CSSR (Conventional Solid State Route) methods. Despite its merits, this process requires high energy and intermediary phase YIP (Yttrium Iron Perovskite) presence during its manufacture. In addition, the formation and controlling mechanism for YIG phase conversion hasn't yielded any conclusive results.